Manajemen Anestesia pada Sindrom Hunter - Nindya Auerkari, Aino; Ramlan, Andi Ade Wijaya (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2019)
Background: Hunter’s syndrome is characterized by congenital metabolic defect due to lysosomal enzyme deficiency. In this syndrome, glycosaminoglycans, a type of mucopolysaccharide cannot be metabolized, and therefore its deposit accumulates in tissue. This substrate deposits progressively over time and eventually interfere with organ function and causes symptoms. Multiple surgeries would be needed to counter its effect throughout patients’ life. Anesthesiologists are expected to prepare the patient for anesthesia, manage intraoperative, and provide postoperative care. The substrate accumulation on airway presents a special challenge for airway management. We describe a case of difficult airway management in a patient with Hunter’s Syndrome who was under enzyme therapy. The main airway challenge are short neck and limited neck extention. Glycosaminoglycans in joints, spine, and heart also require anesthetist’s attention. Drug metabolism in Hunter Syndrome may be different from normal. As this is a rare disease, patients with Hunter’s syndrome is recommended to undergo anesthesia with experienced anesthesiologist in health care facilities with experience in provide care for Hunter’s syndrome.